Mapping Greenhouse Plastic Wastes in the West Region of Portugal - Nanna, Maria (2018)
Plastic materials are used in many applications in agriculture, as greenhouse and tunnel covering films, direct coverings, shading and protective nets, irrigation pipes, fertilizers bags, pots and others. In Mediterranean countries, plastic film is the most common greenhouse covering material. Due to the direct exposure to solar radiation and wind, greenhouse plastic cover needs to be replaced every 6 to 45 months, depending on the material. The huge quantities of plastic waste produced need a proper management in order to avoid environmental and economic impacts. The plastic waste is usually recycled by special companies that collect and treat this waste material. The aim of this study was to apply Geographical Information Systems and photointerpretation techniques to evaluate the amount of plastic waste produced in one of the most important regions of greenhouse production in Portugal, the West Region specifically the Torres Vedras municipality. The methodology has integrated the characterization of the type of plastic covering material and the cartography of the greenhouses land units. It was used the Land Use Map 2007, Bing Map images and administrative boundaries to determine the geographic position and the types of greenhouses. For each administrative unit it was calculated the frequency and total greenhouses area. The identification of the type of plastic material was made by photointerpretation and direct interviews in one Company that sells material for greenhouses in Torres Vedras. The database created allowed to determine the amount of plastic used as greenhouse cover materials and to identify the needs for recycling in this area. The geodatabase produced is a first step to monitoring plastic waste production in time and space.